2019
DOI: 10.4082/kjfm.18.0067
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Vitex agnus-castus Extracts with Placebo in Reducing Menopausal Symptoms: A Randomized Double-Blind Study

Abstract: Background: Menopausal symptoms have remarkable negative effects on women's quality of life, justifying the need to assess various therapeutic options. This research aimed to determine the effectiveness of Vitex agnus-castus extracts in alleviating menopausal symptoms in comparison with that of placebo. Methods: This study was a randomized controlled double-blind clinical trial with a study group of 52 women referred to a clinic in Kermanshah in 2017. The participants were randomly divided into two groups: Vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
0
13
1
Order By: Relevance
“…In another RCT on menopausal women, an 8-week supplementation with 30 mg Vitex decreased the mean scores for the total menopausal disorder, anxiety, and vasomotor dysfunction compared to the placebo. However, other menopausal symptoms such as somatic complications, depression, and sexual dysfunction were not significantly different between the Vitex and placebo groups [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another RCT on menopausal women, an 8-week supplementation with 30 mg Vitex decreased the mean scores for the total menopausal disorder, anxiety, and vasomotor dysfunction compared to the placebo. However, other menopausal symptoms such as somatic complications, depression, and sexual dysfunction were not significantly different between the Vitex and placebo groups [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 reports the results of the main clinical trial studies. Naseri et al [109] reported a reduction in menopausal symptoms after taking V. agnus-castus L. extracts. The authors allocated the participants into two placebo groups and a Vitex-treated group, and then assessed menopausal symptoms before and after an 8-week intervention using the Greene Questionnaire [110].…”
Section: Health-promoting Activities Of Vitex Agnus-castus L In Humamentioning
confidence: 99%
“…Menopause is transition natural period occurs in women life (Norozi et al, 2010). Menopausal symptoms have significant undesirable effects on women quality life (Naseri et al, 2019). During menopause the activities of estrogen and progesterone dramatically reduced (Tanira et al, 2009).…”
Section: Menopausal Symptomsmentioning
confidence: 99%
“…During menopause the activities of estrogen and progesterone dramatically reduced (Tanira et al, 2009). Taking VAC extract as a phytoestrogenic therapy can relieve menopausal symptoms in women (Naseri et al, 2019).…”
Section: Menopausal Symptomsmentioning
confidence: 99%
See 1 more Smart Citation